2015
DOI: 10.1080/17470218.2015.1014821
|View full text |Cite
|
Sign up to set email alerts
|

Native Language Influence on the Distributive Effect in Producing Second Language Subject–Verb Agreement

Abstract: Three experiments were conducted to investigate the distributive effect when producing subject-verb agreement in English as a second language (L2) when the participant's first language either does or does not require subject-verb agreement. Both Chinese-English and Uygur-English bilinguals were included in Experiment 1. Chinese has no required subject-verb agreement, whereas Uygur does. Results showed that the distributive effect was observed in Uygur-English bilinguals but not in Chinese-English bilinguals, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 22 publications
0
21
2
Order By: Relevance
“…The purpose of the present study was to investigate native-Japanese-speaking L2 English speakers' representation and processing of conceptual plurality apart from number agreement, which has been the approach taken by the bulk of the previous research (Foote, 2010;Hoshino et al, 2010Hoshino et al, , 2012Kusnagi et al, 2015;Wei et al, 2015). To achieve this objective, we investigated L2 speakers' comprehension process from the viewpoint of reciprocal verbs, whose processing requires accessing the conceptual plurality of the subject NP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the present study was to investigate native-Japanese-speaking L2 English speakers' representation and processing of conceptual plurality apart from number agreement, which has been the approach taken by the bulk of the previous research (Foote, 2010;Hoshino et al, 2010Hoshino et al, , 2012Kusnagi et al, 2015;Wei et al, 2015). To achieve this objective, we investigated L2 speakers' comprehension process from the viewpoint of reciprocal verbs, whose processing requires accessing the conceptual plurality of the subject NP.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed above, although how L1 and L2 speakers conceptually represent number information in sentence processing has interested many researchers, L2 research has focused almost exclusively on number agreement. Previous studies revealed that L2 speakers processing for number agreement are less likely to be affected by conceptual number than L1 speakers are unless they are highly proficient in the L2 (Hoshino et al, 2010) or their L1 has a number agreement system (Wei et al, 2015). However, the role of conceptual plurality may vary depending on the type of conceptual plurality, for example, conceptual plurality present in collective nouns versus conceptual plurality derived from distributive effects (e.g., see Kusanagi, Tamura, & Fukuta, 2015, for the case of collective nouns).…”
Section: Purpose Of the Present Studymentioning
confidence: 99%
“…Similarly, cross-linguistic differences in grammatical number specification (e.g., trousers is plural in English but singular in Greek) can modulate the computation of L2 subject-verb agreement, providing additional evidence of cross-linguistic influence during L2 production (Hatzidaki et al, 2011). Wei et al (2015) provide further evidence that the absence of L1 number morphology can lead to difficulties integrating conceptual and grammatical number in L2 production. In a task similar to Hoshino et al (2010Hoshino et al ( , 2012, conceptual number failed to modulate highly proficient Chinese L2 English speakers' agreement patterns.…”
Section: Grammatical and Conceptual Number In L2 Productionmentioning
confidence: 88%
“…Because agreement involves the rapid integration of multiple information sources, investigating how L2 speakers produce agreement provides critical insight into the cognitive mechanisms underlying L2 production (e.g., Foote, 2010; Hatzidaki, Branigan, & Pickering, 2011; Hoshino, Dussias, & Kroll, 2010; Hoshino, Kroll, & Dussias, 2012; Nicol & Greth, 2003; Wei, Chen, Liang, & Dunlap, 2015). Key questions include whether L2 speakers rely on similar weightings of grammatical versus conceptual information in both languages and whether the presence of subject-verb agreement in the L1 influences L2 agreement.…”
mentioning
confidence: 99%
See 1 more Smart Citation